2020
DOI: 10.1007/s10143-019-01210-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes and prognostic predictors of 111 pediatric hemorrhagic cerebral arteriovenous malformations after microsurgical resection: a single-center experience

Abstract: Comparison in pediatric hemorrhagic arteriovenous malformations (AVMs) to clarify the long-term neurological outcomes and prognostic predictors after surgical intervention was relatively rare, especially in the selection of surgical timing. The objective of this study was to elucidate these points. The authors retrospectively reviewed the pediatric hemorrhagic AVMs resected in their neurosurgical department between March 2010 and June 2017. The natural history was represented by rupture risk. Neurological outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Our analysis also showed that patients under 40 years of age with poor neurological status at the entrance, average ICH score of 2.67 ± 0.62, and low AVM surgical risk, undergoing early resection of the lesion, had a 3-month poor average mRS (2.47 ± 0.71), while at 1 year the outcome was very favorable (1 ± 0.4). This suggests, in line with other studies, 9,18,25 how in young patients with a high ICH score at the entrance, one or more risk factors consistently related to poor outcome (low GCS, volume clot > 30 mL, infratentorial hemorrhage), and a low-grade Spetzler-Martin malformation, early intervention of evacuation and AVM removal in one single surgical time represents a valid and feasible therapeutic strategy. In a study released in 2020, Deng et al reported a single-center study on 111 hemorrhagic bAVMs in children suggesting that early surgical treatment is preferable following the hemorrhagic presentation.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our analysis also showed that patients under 40 years of age with poor neurological status at the entrance, average ICH score of 2.67 ± 0.62, and low AVM surgical risk, undergoing early resection of the lesion, had a 3-month poor average mRS (2.47 ± 0.71), while at 1 year the outcome was very favorable (1 ± 0.4). This suggests, in line with other studies, 9,18,25 how in young patients with a high ICH score at the entrance, one or more risk factors consistently related to poor outcome (low GCS, volume clot > 30 mL, infratentorial hemorrhage), and a low-grade Spetzler-Martin malformation, early intervention of evacuation and AVM removal in one single surgical time represents a valid and feasible therapeutic strategy. In a study released in 2020, Deng et al reported a single-center study on 111 hemorrhagic bAVMs in children suggesting that early surgical treatment is preferable following the hemorrhagic presentation.…”
Section: Discussionsupporting
confidence: 83%
“…In a study released in 2020, Deng et al reported a single-center study on 111 hemorrhagic bAVMs in children suggesting that early surgical treatment is preferable following the hemorrhagic presentation. 25 Aboukaïs et al 26 found that in grade I bAVMs long-term morbidity is, in the majority of cases, related to the brain damage determined by the hemorrhagic event; only in few cases, this may be linked to AVM resection.…”
Section: Discussionmentioning
confidence: 99%
“…Martinez et al recommended a delayed intervention for at least 4 weeks after the initial hemorrhage. In contrast, Deng et al proposed that short-term outcomes of the early intervention were better, though the long-term outcomes were similar [31]. In this study, most of the neurosurgeons and neurointerventionists recommended early intervention (< 30 days) for ruptured bAVMs; however, the radiosurgeons suggested intervention in the chronic phase or recovery phase and preferably 3 months after bleeding.…”
Section: Current Single-modality and Multi-modality Strategiesmentioning
confidence: 63%
“…In contrast, Deng et al. proposed that short-term outcomes of the early intervention were better, though the long-term outcomes were similar (31). In this study, most of the neurosurgeons and neurointerventionists recommended early intervention (<30 days) for ruptured bAVMs, however, the radiosurgeons suggested intervention in the chronic phase or recovery phase, and preferably 3 months after bleeding.…”
Section: Current Single-modality and Multi-modality Strategiesmentioning
confidence: 64%